Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan pada PT Akasha Wira International Tbk (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the impact of investment decisions, financing decisions, and dividend policies on the firm value of PT Akasha Wira International Tbk during the period of 2014–2023. The research employs a quantitative method with an associative approach. The data used are secondary data in the form of the company's annual financial reports. The independent variables in this study are investment decisions, measured by the Price Earning Ratio (PER), financing decisions, measured by the Debt to Equity Ratio (DER), and dividend policy, measured by the Dividend Payout Ratio (DPR), while the dependent variable, firm value, is measured using the Price to Book Value (PBV). The analysis results indicate that investment decisions have a significant negative impact on firm value, dividend policy has a significant positive impact on firm value, while financing decisions do not significantly affect firm value. Simultaneously, all three variables significantly influence the firm value with a contribution of 60.6%, while the remaining is influenced by other factors. This study suggests that the company should be more selective in making investment decisions and maintain a stable dividend policy to enhance the firm's value in the eyes of investors.